A zinc–air cell employing a porous zinc electrode fabricated from zinc–graphite-natural biodegradable polymer paste - Othman, Raihan; Abdul Hamid, Yahaya; Arof, Abdul Kariem (Kluwer Academic Publishers, Netherlands, 2002)
Porous zinc anodes have been fabricated from a mixture of zinc and graphite powder using gelatinized agar solution as the binding agent. Agar is a biodegradable polysaccharide polymer extracted from marine algae. The graphite content and the agar solution concentration were varied to find the best electrode composition. Zinc–air cells were fabricated using the porous zinc anode, a commercially available air cathode sheet and KOH electrolyte in the form of elastic jelly granules. The electrode performance was evaluated from the zinc–air cell galvanostatic discharge capability. In the cell design, a thin agar layer was introduced between the electrode-gelled electrolyte interfaces, resulting in substantially improved cell discharge performance. The inclusion of particulate graphite into the electrode did not enhance the electrode performance due to the formation of a graphite-rich layer, which obscured the electrode porosity. A zinc–air cell employing the optimized porous zinc electrode demonstrated a capacity of 2066 mA h and specific energy density of 443 Wh/kg.